2022
DOI: 10.1002/cc.20523
|View full text |Cite
|
Sign up to set email alerts
|

Roadmap to emergency remote teaching

Abstract: This chapter captures the authors' voices as faculty who were abruptly required to learn how to teach courses remotely in response to the COVID-19 pandemic. They share how they successfully made changes and stayed committed to maintaining high standards in an online environment. Based on these experiences, they present recommendations for adaptations of active learning techniques from face-to-face (F2F) courses to online equivalents. Their roadmap to success focuses on key factors that contributed to increased… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“… Theme III refers to "Technostress related to Professional development of teachers mechanisms", including their lack of technical skills, lack of motivation to use technology, the poor pedagogical support for teaching with technology during teacher education etc. This implies that the support teachers need to better deal with technostress spans several areas, ranging from professional development opportunities to technical, peer and administrative support, and access to mental health resources (Whalen, 2020;Dennis, 2021;Daneshmand et al, 2022). Access to training and professional development programs can help teachers develop the competencies they need to effectively integrate technology into their classroom.…”
Section: Technostress In Online Education: the Positive Learn Projectmentioning
confidence: 99%
“… Theme III refers to "Technostress related to Professional development of teachers mechanisms", including their lack of technical skills, lack of motivation to use technology, the poor pedagogical support for teaching with technology during teacher education etc. This implies that the support teachers need to better deal with technostress spans several areas, ranging from professional development opportunities to technical, peer and administrative support, and access to mental health resources (Whalen, 2020;Dennis, 2021;Daneshmand et al, 2022). Access to training and professional development programs can help teachers develop the competencies they need to effectively integrate technology into their classroom.…”
Section: Technostress In Online Education: the Positive Learn Projectmentioning
confidence: 99%
“…Following the person-centered approaches, the present study seeks to analyze data from lecturers during the first COVID-19 lockdown to classify them based on how they used educational technology for ERT. Qualitative studies have shown how differently faculty members have experienced the transition to ERT [4][5][6]23]. In this study, we use quantitative data and analyses to enrich these research findings and highlight the importance of individual experiences and progress related to digital transformation in higher education.…”
Section: Introductionmentioning
confidence: 99%
“…For example, lecturers for whom teaching in an online-only environment was new, used educational technology trying to replicate their conventional teaching. The need for more student-centered approaches to teaching and the benefits of educational technology to enhance learning was not visible or attainable to the initial ERT [3][4][5].…”
Section: Introductionmentioning
confidence: 99%
“…As the demand for online courses increases, faculty and staff are challenged to continue to support student success while maintaining student learning outcomes in an online environment (see Chapter 3 by Daneshmand et al. (2022) in this volume). Our early online STEM educational experiences put us in a position to be faculty agents of change.…”
Section: Introductionmentioning
confidence: 99%
“…Online education is one of the fastest-growing trends in higher education (Moloney et al, 2010), and the pandemic that started in 2020 only increased the number of online courses available to students. As the demand for online courses increases, faculty and staff are challenged to continue to support student success while maintaining student learning outcomes in an online environment (see Chapter 3 by Daneshmand et al (2022) in this volume). Our early online STEM educational experiences put us in a position to be faculty agents of change.…”
Section: Introductionmentioning
confidence: 99%